Bursa Malaysia’s CSR initiatives / Norshafaf Jailani - Jailani, Norshafaf (2008)
Purpose The purpose of this paper is to study on how Bursa Malaysia responds towards heightened concerns in social responsible and whether the stakeholders are well involved in Bursa’s CSR practices. Researcher has signaled the need for CSR framework and model of initiatives to explore ways in which strategic CSR can be integrated into business structures and processes in a sustainable way. Given this sea change in the corporate environment, companies want to increase their ability to manage their profits and risks, and to protect the reputation of their brands.